Využití peptigelu s nanovlákny k léčbě defektů kostní tkáně - Srnec, R; Divín, R; Škorič, M; Snášil, R; Krbec, M; Nečas, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
INTRODUCTION Traumatic bone injuries or pathological processes may sometimes result in very extensive bone defects. Currently, the standard procedure applied in clinical humane as well as veterinary medicine to fill a bone defect is the autogenous bone graft which, however, necessitates a more invasive procedure for the patient and in the cases of extensive defects it fails to provide adequate amount of graft. Synthetic bone replacements can be used with no further burden for the patient and can simultaneously be used as the carriers for bioactive molecules or therapeutic drugs. For clinical use, an easy and simple application is one of the requirements that have to be taken into consideration. These requirements are best satisfied by preparations in the form of gel, which may be injected into the defects of various shapes even through minimal surgical approach. MATERIAL AND METHODS Synthetic transparent PGD-AlphaProA hydro-peptide-gel was used as a basis to develop a composite hydrogel scaffold. This gel was enriched by cryogenically ground poly- -caprolactone nanofibers (PCL) in a ratio of 1 ml of gel to 16 μg of nanofibres. In experimental animals (laboratory rat Wistar, n=20), a single regular circular defect of 1.5 mm in diameter was drilled by a low speed drill machine across the whole width of distal femur diaphysis, identically in both the hind legs. In the right hindleg, this defect was filled by injection of 0.05 ml of the composite peptide gel with nanofibers (experimental defect). In the contralateral limb a similar defect was left untreated, without filling (control defect), for spontaneous healing. The group of experimental animals was subsequently divided into four sub-groups (A, B, C, D) for the purpose of further follow-up. One week after the surgical implantation, in the first group of experimental animals (Group A; n = 5) lege artis euthanasia was performed, a radiological examination of both the hind legs was carried out and a sample of the bone from both the control and experimental defect was collected for histologic examination. The other groups of experimental animals were evaluated similarly at 2, 4 and 6 weeks after the surgical procedure (Group B, C, D; n = 5). These groups of experimental animals were assessed using various histological techniques by two independent pathologists. RESULTS A difference between the control and the experimental bone defect was observed only at the healing stage at two weeks after the implantation, when a tendency for greater formation of new bone trabeculas was seen in the defect treated with the composite hydro-peptide-gel with PCL nanofibers. The results show a slightly higher angiogenesis and cellularity at the bone defect site with an increase of newly formed bone tissue and faster colonisation of lamellar bone structures by bone marrow cells at early stages of the healing process (1-2 weeks old defect). In the experimental and control groups, at the later stage of healing (4-6 weeks old defect), the process of healing and bone modelling at the defect site shows no detectable morphological differences. CONCLUSIONS The experimental use of hydro-peptide-gel with PCL nanofibers in vivo in laboratory rats shows very good applicability into the defect site and, compared to the untreated defect within two weeks after the implantation, accelerates the bone healing. This fact could be an advantage especially at the early stage of healing, and thus accelerate the healing of more extensive defects. Key words: peptide gel, polycaprolactone, PCL, replacement, bone, healing, scaffold, nanofibers, biomaterial.
Keywords: Animals; Fracture Healing; buněčné struktury; Rats, Wistar; nanovlákna; biokompatibilní materiály; hojení fraktur; Bone Transplantation; nemoci kostí; kosti a kostní tkáň; Bone Substitutes; Nanofibers; Femur; Models, Animal; Polyesters; Bone Diseases; Cellular Structures; femur; Biocompatible Materials; látky indukující angiogenezi; Angiogenesis Inducing Agents; krysa rodu Rattus; transplantace kostí; kostní náhrady; zvířata; polyestery; Bone and Bones; Rats; modely u zvířat; potkani Wistar